Beyond Place: Network Effects Versus Jurisdiction and Sovereignty - Szigeti, Péter D. (Oxford University Press (OUP), 2025)
Anxieties about the viability and future of the liberal international order have been multiplying in both scholarly discussions and the popular press. But what does the "coming apart of the liberal international order" actually mean? Some commentators point to sanctions and tariffs that are destroying free trade; and some are focusing on democratic backsliding, the rise of populism and the crumbling of human rights protections (especially in international migration). An arguably more fundamental, and equally worrying, shift is discussed in three recent books: the end of territorial jurisdiction, and with it, a deep uncertainty in what independence, sovereign equality, nonintervention, self-determination, and other fundamental concepts of peaceful coexistence can mean in the twenty-first century. Because thirty or so banks control almost all of international finance and the United States controls the dollar and the hegemonic currency of international trade, the difference between territorial jurisdiction and extraterritorial jurisdiction has disappeared in global trade and finance, as well. Henry Farrell and Abraham Newman provide a readable and popular introduction; Pierre-Hugues Verdier explains in detail the mechanisms of international financial law; and Cornelia Woll tries to integrate these events into legal theory and doctrine.